A meditation on what a post-human education might look like: "Touching something beyond myself and my time" - William Boyd; Louise Horstmanshof (University of Aberdeen, School of Education, 2019)
Two academics meditate on the state of education and seek wisdom from the poets and other creative writers to illuminate their unknowing. We acknowledge the growing disquiet that all is not working well in education. Is the education on offer fit for purpose? Does it prepare students for a world of disappearing professions, spreading automation where the implications of the next disruption are unknown, unimaginable? Does it meet the urgent needs of the Anthropocene and of changing social structures of a post-human world? We sense the need to reconsider the contemporary everyday. We reach back to the past, to nature, to ground ourselves in the senses of what is real, and true, as a way to open a door to this unfathomable future. In doing so, we notice distinctions, boundaries and categories that trap us in the present, yet point to potential futures. In shining a light on these, we return to the conviction that a future education needs to be useful. An education of the future needs to return to the world and a natural order where we relinquish our human dominance. We share the questions that arise out of our meditation on the challenges of an education of the future. We hope these questions will 'stimulate, provoke, inform and inspire' others to collaborate on the answers.